Analisis Kinerja Keuangan Pemerintah Daerah Kota Jambi - Deva Alvina; Amri Amir; Yudi Yudi (Jurnal Akuntansi & Keuangan Unja, 2018)
This research aims to analyze financial performance local governments of Jambi city. The results on the effectiveness ratio of PAD of Jambi shows that the financial performance of Jambi city government has been effective, the efficiency level of jambi municipal efficiency is less efficient, the Jambi city government's harmony ratios show the amount of operating expenditure is greater than the capital expenditure, Operations such as grant expenditure and social assistance expenditure indicate that the proportion of these two expenditures is greater at the time of the election of the Head of Region, the growth ratio PAD Local Government of Jambi City showed positive. Capital expenditure growth, average operating expenditure is 38,62% and 11,37%. the growth of local government of Jambi city shows a positive result, the level of financial independence of jambi city is still very dependent on funds transfer from the center and province. Keywords: Regional Autonomy, Financial Performance, Regional Financial